Effects of different training options on the basic movements physical fitness 4-year-old girls with different motor asymmetry - L. L. Galamandjuk (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : to determine the effectiveness of different training options basic movements in terms of physical fitness girls with different orientation manual motor asymmetry (MMA). Material : the study involved 53 girls with ambidexterity: 68 - on the right, 62 - left oriented MMA. Age - 4 years. Results : there is a significant improvement in absolute muscle strength, speed-strength, coordination and cyclic locomotion tossing on the leading and non-leading range of hands regardless of the approach to teaching basic movements in girls. At the same time the increase of these qualities and the coordination of the throws on the accuracy of each hand is significantly higher when using one of the options "symmetric" approach. If you are using one of the options "symmetric" approach to teaching basic movements focus MMA defines the features of the development of physical qualities. Conclusions : regardless of the direction of MMA both versions of "symmetric" approach to improve the effectiveness of traditional indicators of physical fitness; the effectiveness of the first among themselves no different.